2020
DOI: 10.1596/1813-9450-9386
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Internet and Household Welfare in Senegal

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Mobile internet coverage also reduces the proportion of households below the national poverty line by 5-7 percentage points. These results are consistent and similar in magnitude to recent studies for Nigeria (Bahia et al, 2020), the Philippines (Blumenstock et al, 2020), and Senegal (Masaki et al, 2020). 4 These e↵ects are heterogeneous, with higher welfare gains in urban areas and among households headed by female, poorer, or less-educated household heads.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mobile internet coverage also reduces the proportion of households below the national poverty line by 5-7 percentage points. These results are consistent and similar in magnitude to recent studies for Nigeria (Bahia et al, 2020), the Philippines (Blumenstock et al, 2020), and Senegal (Masaki et al, 2020). 4 These e↵ects are heterogeneous, with higher welfare gains in urban areas and among households headed by female, poorer, or less-educated household heads.…”
Section: Introductionsupporting
confidence: 89%
“…Individual coverage of mobile broadband is defined as the provision of 3G coverage, which enables highspeed access to the Internet, and excludes 2G coverage as it only provides for limited internet browsing and applications.4Bahia et al (2020) shows that having at least one year of mobile broadband coverage increases total consumption by 5.8 percent, and up to 9.2 percent after three years of more of coverage Masaki et al (2020). find that total consumption among households covered by 3G technology is about 14 percent greater than the total consumption of households not covered by 3G Blumenstock et al (2020).…”
mentioning
confidence: 99%
“…Besides these potential direct welfare gains of expanding competition in the ICT market in Ethiopia, the potential marginal effects on adoption may have additional indirect welfare implications because mobile phones are transitioning from simple communication tools to stand-alone service delivery platforms and because digital technologies have the potential of significantly reducing the costs of economic activities (Goldfarb and Tucker 2019;Rennhoff and Routon 2016). Recent research on Africa, for example, has shown the importance of internet access in poverty reduction, increasing household consumption, and improving labor market outcomes (Bahia et al 2020;Hjort and Poulsen 2019;Masaki, Granguillhome Ochoa, and Rodríguez-Castelán 2020;Masaki, Raja, and Rodríguez-Castelán 2020). Furthermore, if complementary reforms in other sectors are undertaken, such as the financial sector, mobile devices would have the potential to enable poor people to lower transaction costs, raise access to credit, and apply risk mitigation safeguards, leading to a reduction in vulnerability and poverty (Jack and Suri 2014;Wieser et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Besides these potential direct welfare gains of expanding competition in the ICT market in Ethiopia, the potential marginal effects on adoption may have additional indirect welfare implications because mobile phones are transitioning from simple communication tools to stand-alone service delivery platforms and because digital technologies have the potential of reducing significantly the costs of economic activities (Goldfarb and Tucker 2019;Rennhoff and Routon 2016). Recent research on Africa, for example, has shown the importance of internet access in poverty reduction, increasing household consumption, and improving labor market outcomes (Bahia et al 2020;Hjort and Poulsen 2019;Masaki, Granguillhome Ochoa, and Rodríguez-Castelán 2020;Masaki, Raja, and Rodríguez-Castelán 2020). Furthermore, if complementary reforms in other sectors are undertaken, such as the financial sector, mobile devices would have the potential to enable poor people to lower transaction costs, raise access to credit, and apply risk mitigation safeguards, leading to a reduction in vulnerability and poverty (Jack and Suri 2014;Wieser et al 2019).…”
Section: Discussionmentioning
confidence: 99%